Penetrating Stab Injury to the Thoracic Spinal Cord: A Case Report - Kumar, Sushil; Tiwary, Ravi; Desai, Ashish; Garg, Amit (Indian Journal of Neurotrauma, 2015)
Stab injuries to the spinal cord due to knife are rare. Usually the knife slips into the interlaminar space to injure the cord incompletely. We report a 24-year-old man who was stabbed by robber in the thoracic region. He presented with the Brown-Séquard plus syndrome. Knife penetrated the lamina, driving the bony chip into extradural space injuring the dura and cord. The patient was subjected to laminectomy and duraplasty with fascial graft. He showed good improvement and has joined his occupation.
Keywords: penetrating spinal cord injury; stab wound; Brown-Séquard plus syndrome